ANALISIS EKSPERIMENTAL: PERBANDINGAN MEDIA PEMBELAJARAN DAN TEKANAN WAKTU TERHADAP KETEPATAN MENJAWAB SOAL AKUNTANSI KEUANGAN BERBASIS TEORI KOGNITIF PEMBELAJARAN MULTIMEDIA - Rr. Puruwita Wardani; Susanna Hartanto (Jurnal Riset Akuntansi, 2025)
This study examined the improvement of students' understanding in studying financial accounting by considering the learning method with time pressure on students' accuracy in answering questions. The use of multimedia is expected to minimize cognitive load, especially in time constraints. The purpose of this study is to analyze the role of text and video media and time pressure in their influence on the accuracy of answering financial accounting questions. This study is a 2x2 factorial design experimental method. The dependent variable is the accuracy in answering accounting questions, while the independent variables are learning materials in the form of text or video, and time pressure in completing questions. The results of this experimental approach are that students who learn using video media will show higher accuracy in answering financial accounting questions than students who learn using text media is not proven. Both text and video, can support students in solving accounting problems. Students who are in low time pressure conditions will have higher accuracy in answering questions than students in high time pressure conditions because time pressure has increased students' cognitive load so that students are not calm in answering questions and resulting in inaccuracy in answering accounting case questions.